DIRECTIVE HIGH GAIN MICROSTRIP PATCH ARRAY ANTENNA FOR 5G APPLICATION - Muhammad, Idris N.; Musa, Zaharadden (FUDMA JOURNAL OF SCIENCES, 2020)
With the recent development in wireless communication, low cost, compact, low profile antenna is required for the maintaining of high frequencies performance. Microstrip patch antennas are the fundamental component of every wireless communication system. It has broad practical application in wireless communication because it offers ease, low cost of integration and fabrication with feeding network. Triangular, rectangular and square are the most common shapes of the microstrip antenna which are usually made up of materials of gold or copper. However, the main drawback of microstrip patch antenna is that, it has very narrow bandwidth. This effect can be reduced to the lower level by make use of different feeding method, array configuration, ground plane and dielectric materials. In this research paper a directive high gain microstrip patch array antenna for 5G application is presented. A single antenna element designed based on microstrip technology, which is later be made into a number of arrays to improved gain and bandwidth. Transmission line model method is used to calculate the antenna dimension designed to resonate at 10GHz. To achieved the improve gain; multiple number of array element has to be arranged either in series or in parallel. A microstrip feed line is designed using a 3dB power divider to feed each of the elements of the antenna array. Simulations is carried out using microwave studio (CST) and the antenna performance was studied based on gain, bandwidth and radiation pattern. Fabrication was carried out on readily available FR4 substrate of thickness 1.6mm and
Keywords: 5G wireless communication, microstrip patch antenna, array element, DirectivityBandwidth